Shafts of a pair of columns which once surmounted a torana - Temples of India Project Team (Jio Institute, 2024)
Shafts of a pair of columns that once surmounted a torana or doorways at the entrance of the temple complex. Verse-12 of the Harshnath stone inscription records ‘Resembling (in height) the peak of Meru, it is pleasant on account of an excellent torana-dvara (arched doorway), and well-carved Nandi, and is full of manifold objects of enjoyment.’ The mentioned shafts formed the arched entrance described in the verse.